Financial crime and knowledge workers: an empirical study of defense lawyers and white-collar criminals - Gottschalk, Petter (Palgrave Macmillan, 2014)
Introduction 1. White-Collar Criminals and Crime 2. White-Collar Crime Defense Lawyers 3. White-Collar Crime Defense Strategies 4. Lawyers as Knowledge Workers 5. Theoretical Perspectives on Defense Lawyers 6. Empirical Study of White-Collar Lawyers 7. Law Firms as Knowledge Organizations 8. Knowledge Management in Law Firms 9. Prosecution in Court Conclusion